2020
DOI: 10.1038/s41598-020-70211-x
|View full text |Cite|
|
Sign up to set email alerts
|

Comparable antibacterial effects and action mechanisms of silver and iron oxide nanoparticles on Escherichia coli and Salmonella typhimurium

Abstract: The current research reports the antibacterial effects of silver (Ag) and citric acid coated iron oxide (Fe 3 O 4 ) NPs on Escherichia coli wild type and kanamycin-resistant strains, as well as on Salmonella typhimurium MDC1759. NPs demonstrated significant antibacterial activity against these bacteria, but antibacterial effect of Ag NPs is more pronounced at low concentrations. Ag NPs inhibited 60–90% of S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 36 publications
1
44
0
Order By: Relevance
“…The main antimicrobial mechanism of Eucalyptus globulus EO is the membrane cell damage and interference with proton pumps and electrolyte channels [ 105 , 106 ]. On the other hand, magnetite nanoparticles are known for their cell wall damage properties, as well as stimulation of the intracellular release of reactive oxygen species (ROS), which interfere with vital mechanisms, such as cell division and signaling [ 107 ]. Improved antimicrobial activity of synthetic [ 108 , 109 ] and natural [ 110 , 111 ] antibiotics were reported when conjugated with magnetite nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The main antimicrobial mechanism of Eucalyptus globulus EO is the membrane cell damage and interference with proton pumps and electrolyte channels [ 105 , 106 ]. On the other hand, magnetite nanoparticles are known for their cell wall damage properties, as well as stimulation of the intracellular release of reactive oxygen species (ROS), which interfere with vital mechanisms, such as cell division and signaling [ 107 ]. Improved antimicrobial activity of synthetic [ 108 , 109 ] and natural [ 110 , 111 ] antibiotics were reported when conjugated with magnetite nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The study of antibacterial activity of GS and ultrasound-treated Ag NPs was performed on S. typhimurium MDC1759 and S. aureus MDC5233 strains (Microbial Depository Center, National Academy of Science, Yerevan, Armenia). The mentioned strains were grown in Nutrient Broth (NB) media at 37 °C and pH 7.5 (Gabrielyan et al 2020 ). Anaerobic conditions were maintained as described (Gabrielyan et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The high demand for Ag NPs is conditioned by the commercial utilization of Ag NPs in optics, electronics, catalysis, household items, and a broad range of medical applications (Ge et al 2014 ; Gabrielyan and Trchounian 2019 ). Ag NPs are known for their broad-spectrum antimicrobial and antiviral activities (Gabrielyan and Trchounian 2019 ; Gabrielyan et al 2020 ). These NPs are widely applied in different industries in the disinfection of ailments, water, medical instruments, etc.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, iron oxide’s antimicrobial activity [ 3 , 5 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] and the respective mechanism of action have been studied. Analogously to ecotoxic properties of iron oxide NPs, their antimicrobial properties are not comparable to powerful antimicrobials such as copper and silver compounds that act at a few mg/L levels [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there was more strong effect to E. coli (a gram-negative bacterium) than to E. hirae (a gram-positive bacterium), probably due to the differences in the bacterial cell wall structure. The same authors in their following paper reported more remarkable antibacterial effects of citric acid coated magnetite Fe 3 O 4 NPs towards E. coli : 250 mg/L of citric acid coated Fe 3 O 4 NPs inhibited the growth of E. coli by 2-fold (a bacteriostatic effect), whereas the kanamycin resistant E. coli was inhibited slightly more at up to 3-fold [ 43 ]. Almost similar results (MIC = 150 mg/L) were reported for hematite Fe 2 O 3 NPs towards E. coli and Vibrio cholerae [ 21 ].…”
Section: Introductionmentioning
confidence: 99%